(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Purpose: The purpose of this study is to understand the participation process and their value and of participants who participated in Reformer Pilates.Method: For this purpose, 10 Person who attended Reformer Pilates at Deajeon were selected as study participants based on Purposeful Sampling. The results of data analysis according to the method suggested by Stake(2005) by collecting data throug in-depth interviews, observations and note are as follows.Results: First 'Meet the Reformer', including 'Clumsy Reformer movement' and 'confusion Period ' were derived. Second the aspects of‘Proficient of Instrument operation’ including 'Unity of Reformer and I' and ' adaptation Period' were revealed. Last‘Level-up with the help of Reformer’ and ‘fall in Reformer movements’ including ‘dependence period’ were confirmed. Conclusion: This result of this study will be a good reference for the Pilates workout to promote their positive interest in Pilates Studio and to develop effective systems and programs that will contribute to the development of Pilates workout.